Aptamer-based approaches for in vitro molecular detection of cancer - Hadi Bakhtiari; Abbas Ali Palizban; Hossein Khanahmad; Mohammad Reza Mofid (Wolters Kluwer Medknow Publications, 2020)
Cancer is typically associated with abnormal production of various tumor-specific molecules known as tumor markers. Probing these markers by utilizing efficient approaches could be beneficial for cancer diagnosis. The current widely-used biorecognition probes, antibodies, suffer from some undeniable shortcomings. Fortunately, novel oligonucleotide-based molecular probes named aptamers are being emerged as alternative detection tools with distinctive advantages compared to antibodies. All of the existing strategies in cancer diagnostics, including those of in vitro detection, can potentially implement aptamers as the detecting moiety. Several studies have been performed in the field of in vitro cancer detection over the last decade. In order to direct future studies, it is necessary to comprehensively summarize and review the current status of the field. Most previous studies involve only a few cancer diagnostic strategies. Here, we thoroughly review recent significant advances on the applications of aptamer in various in vitro detection strategies. Furthermore, we will discuss the status of diagnostic aptamers in clinical trials.